The effect of grazing on granivory patterns in the temperate Monte Desert, Argentina - Sassi, Paola Lorena (2006)
Structural variations result in a marked heterogeneity of processes in arid environments. Disturbances have noticeable impacts on ecosystems, and a solid way of assessing their effect is to analyze how ecological processes operate. In deserts, granivory has been considered as a keystone process. The objective of our study was to determine the effect of domestic grazing on seed removal rates by birds, ants and rodents as an indirect measure of the process of granivory. This study was carried out in grazed and ungrazed habitats in the central Monte desert ecoregion in Argentina, during February and July 2002. We analyzed three major habitats: mesquite forest, creosotebush shrubland, and sand dunes under two different treatments (grazed, ungrazed). We found significant effects of grazing and non-grazing treatments on total seed removal rates, among granivorous taxa, as well as interactions with season and habitats. Ants and birds were the taxa that differed most under grazing pressure whereas seed removal by rodents showed no significant responses towards grazing. In conclusion, grazing affects plant structure and the assemblage of granivorous taxa, which in turn translates to the granivory process, adding another source of variation to the seed removal patterns reported for the temperate Monte desert.